Rivaroxaban versus warfarin: differential effects on oxidative stress and fibrinolytic markers in atrial fibrillation - Reis, Helton Jose; Costa, Luana Bernardes Xavier; Martins, Gabriela Lopes; Duarte, Rita Carolina Figueiredo; Costa, Luma Clara Martins; Figueiredo, Estêvão Lanna; Silveira, Francisco Rezende; Coelho, Nathália Greco; Carvalho, Maria das Graças; Vieira, Luciene Bruno; Reis, Edna Afonso; Gomes, Karina Braga; et al. (Frontiers in Pharmacology, 2026)
BackgroundAtrial fibrillation (AF) is a cardiac arrhythmia characterized by disorganized atrial electrical activity, resulting in ineffective mechanical contraction and a heightened propensity for intra-atrial thrombus formation. The underlying pathophysiology is multifactorial, involving a complex interplay of pro-fibrotic, inflammatory, and pro-thrombotic pathways, notably oxidative stress and dysregulation of the fibrinolytic system. Given that these mechanisms remain incompletely elucidated, this study sought to investigate the association between biomarkers of oxidative stress and antifibrinolytic activity in AF patients treated with the oral anticoagulants warfarin or rivaroxaban, in comparison to a healthy control cohort.MethodsA total of 85 AF patients—38 on rivaroxaban and 47 on warfarin—were enrolled alongside 62 matched healthy controls. Cellular metabolic activity was assessed via MTT [3-(4,5-Dimethylthiazol-2γl)-2,5-Diphenyl Tetrazoline Bromide] assay measured by spectrophotometry. Serum concentrations of thiobarbituric acid reactive substances (TBARS, a marker of lipid peroxidation), plasminogen activator inhibitor-1 (PAI-1), and thrombin-activatable fibrinolysis inhibitor (TAFI) were quantified using enzyme-linked immunosorbent assay (ELISA).ResultsThe rivaroxaban group exhibited significantly greater MTT absorbance, indicative of enhanced cellular metabolic activity, and significantly lower circulating TAFI levels compared to the warfarin group.ConclusionThese results suggest that in patients with AF, rivaroxaban may provide pleiotropic benefits beyond anticoagulation, potentially by augmenting cellular antioxidant mechanisms and suppressing antifibrinolytic activity.